Tailored antisense oligonucleotides for ultrarare CNS diseases: an experience-based best practice framework for individual patient evaluation - Schüle-Freyer, Rebecca; Graessner, Holm; Aartsma-Rus, Annemieke; van Roon-Mom, Willeke M. C.; Synofzik, Matthis (Molecular therapy. Nucleic Acids, 2025)
Individualized mutation-specific RNA therapies offer promise, in particular, for individuals with ultrarare neurological diseases that affect only few families or even single patients worldwide. Outside traditional drug development pathways, however, clinicians and scientists face the challenge of systematically evaluating whether individual patients with severe ultrarare diseases might be eligible for and potentially benefit from such approaches. This complex evaluation involves biological, clinical, psychological, and ethical aspects. Based on the experience of the 1 Mutation 1 Medicine (1M1M) consortium, we here propose a best practice framework that enables the systematic evaluation of individual patients for tailored genomic therapies, using transparent criteria to comprehensively assess each individual’s benefit-risk balance. By example of individually tailored antisense oligonucleotide approaches in neurology, this framework takes into account characteristics of the (1) underlying variant, (2) underlying disease, and (3) individual patient. It thereby allows a systematic, balanced, fact-based evaluation that appreciates the full complexity and preferences of each individual patient, performed by a multi-stakeholder treatment board. This operational framework will thus pave the way for systematic, rational patient-centric evaluation and decision-making in the rapidly evolving field of individualized “n-of-1” precision genomic medicine in clinical neurology.